womeninoss.com: Supporting women participation in OSS communities with an online platform - Moreira, Gessyca; Freitas, Juliana; Burvant, Sarah; Sengchiam, Caitlynn; Paula, Suelen M. de; Fronchetti, Felipe (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.11023, 2025)
Women are severely underrepresented in open-source software (OSS) communities, accounting for only 10% of overall contributors [20]. Unlike their male counterparts, women often face genderspecific barriers that diminish their participation in open source, including issues such as impostor syndrome, gender bias, and a lack of visible role models [20]. These challenges create a compounding effect that perpetuates their underrepresentation and limits their contributions within OSS projects, highlighting the need for interventions that can foster more inclusive and equitable environments. To support women to overcome these challenges and promote their participation in OSS, we propose the development of womeninoss.com: an online platform designed to educate, empower, and support women’s involvement in open-source communities. Designed to support both newcomers and maintainers in OSS, our web-based platform offers research-driven insights on gender inclusion in open source, along with a suite of practical tools to help individuals and communities increase and sustain women’s collaboration in OSS projects. In a preliminary evaluation of our platform, we invited 15 software developers to provide feedback on its significance, content relevance, and potential impact on fostering women’s participation in OSS. Our preliminary findings suggest that the platform was well-received, with participants highlighting its potential to serve as a valuable resource for both newcomers and community maintainers. Demo video:  https://zenodo.org/records/15465699